231k views
4 votes
Wyatt claims that _ is equivalent to _ Which statement about his claim is true in every aspect?

Wyatt claims that _ is equivalent to _ Which statement about his claim is true in-example-1

2 Answers

5 votes

Answer:

D in short

Explanation:

Ed2021

User Gerhardt
by
5.1k points
2 votes

Answer:

The statement that is true in every aspect regarding his claim is:

  • False, because when combined in this manner, the alternating signs of the series are lost ( Wyatt ignored the negative in the first factor)

Explanation:

The series is given as:


\sum_(n=0)^(3) (-(1)/(3))^n\cdot 9

which could also be written by:


\sum_(n=0)^(3) (-(1)/(3))^n\cdot 9=\sum_(n=0)^(3) (-(1)/(3))^n\cdot 3^2\\\\\\\sum_(n=0)^(3) (-(1)/(3))^n\cdot 9=\sum_(n=0)^(3) (-1)^n((1)/(3))^n\cdot 3^2

i.e.


\sum_(n=0)^(3) (-(1)/(3))^n\cdot 9=\sum_(n=0)^(3) (-1)^n\cdot 3^(-n)\cdot 3^2\\\\\\\sum_(n=0)^(3) (-(1)/(3))^n\cdot 9=\sum_(n=0)^(3) (-1)^n\cdot 3^(2-n)

which is not equivalent to:
\sum_(n=0)^(3) 3^(2-n)

Since, on expanding the actual series we get the sum as:


\sum_(n=0)^(3) (-(1)/(3))^n\cdot 9=(-(1)/(3))^0\cdot 9+(-(1)/(3))^1\cdot 9+(-(1)/(3))^2\cdot 9+(-(1)/(3))^3\cdot 9\\\\\\=9-(1)/(3)* 9+(1)/(3^2)* 9-(1)/(3^3)* 9\\\\\\=9-3+1-(1)/(3)\\\\\\=(22)/(3)

Now, the expansion of:


\sum_(n=0)^(3) 3^(2-n) is:


\sum_(n=0)^(3) 3^(2-n)=3^2+3^1+3^0+3^(-1)\\\\\\=9+3+1+(1)/(3)=(40)/(3)

User Tanvir Durlove
by
6.3k points